The effect of processing parameters on fermentable sugar production from typical Malaysian starch-based waste via acid hydrolysis - Akil, Mustapha; Awang Biak, Dayang Radiah; Ahamad, Intan Salwani; Mohamad, Rosfarizan; Kamarudin, Suryani (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2010)
Production of alternative carbon source from waste has become interesting since most of the wastes end up being discarded. The occurrence of abundant amount of some wastes in Malaysia such as sago effluent, banana peel and potato peel can be used as alternatives carbon source. They can be hydrolyzed to produce fermentable sugar mainly glucose. The objective of this study was to produce fermentable sugar via diluted sulphuric acid hydrolysis. Three operating parameters were varied namely acid concentration (v/v) (2%, 4% and 6%), processing time (20, 40 and 60 minutes) and operating temperatures (105°C and 121°C). High performance liquid chromatography (HPLC) was used to identify and quantify the amount of sugar produced. The results were plotted using contour plot (MINITAB) to identify the optimum processing region. The optimal condition selected was 4% (v/v) H2SO4, 40 minutes and 105°C which can produce glucose about 62% (w/w) from sago effluent, 6% (v/v) H2SO4, 20 minutes and 121°C which can produce about 20% (w/w) of glucose from banana peel and 4% (v/v) H2SO4, 20 minutes and 105°C which can produce about 40% (w/w) of glucose from potato peel. In conclusion, Malaysian starch-based wastes have large potential to be reutilized as one of alternative carbon source.